PENGARUH PERBANDINGAN KONSENTRASI FASE MINYAK SALEP EKSTRAK IKAN GABUS (Channa striata) TERHADAP LAMA PENYEMBUHAN LUKA SAYAT PADA TIKUS PUTIH GALUR WISTAR (Rattus norvegicus) - KHAIRUNNISA KHAIRUNNISA; ILHAM HARIAJI (JURNAL ILMIAH MAKSITEK, 2022)
Fish is one of the largest natural resources in Indonesia and is useful as a source of protein and a source of natural medicinal ingredients, one of which is snakehead fish. Empirically, snakehead fish is often consumed as a side dish after childbirth and as a medicine for wounds caused by sharp objects. Wounds are the loss or destruction of part of the body's tissues. This condition can be caused by sharp or blunt trauma, temperature changes, chemicals, explosions, electric shocks, or animal bites. The wound healing process is not only limited to local regeneration processes but is also influenced by endogenous factors such as age, nutrition, immunology, use of drugs, and metabolic conditions. During the healing process, adequate intake of nutrients such as carbohydrates, protein, fat, and micronutrients is necessary. Therefore, it is necessary to conduct a study to determine the concentration of snakehead fish (Channa striata) extract oil phase ointment that has the greatest effect on accelerating the healing process of cuts in white rats of the Wistar strain (Rattus norvegicus). Objective: To determine the effective concentration of snakehead fish (Channa striata) oil phase ointment on the healing time of cuts in white rats of the Wistar strain (Rattus norvegicus). The research method is a true experiment with a post-test only control group design. The sampling technique used is simple random sampling, where the sample subjects are selected by means of each subject being numbered, and some of them are selected with the help of a random number table. The results show that a p value >0.05 was found between the negative control group and the 20% concentration group, a p value <0.05 between the negative control group and the 40% concentration group, and a p value <0.05 between the 20% concentration group and the 40% concentration group. That is, snakehead fish ointment with a concentration of 40% has the highest effectiveness. The conclusion of this research is that the increase in the concentration of snakehead fish (Channa striata) oil-phase ointment was directly proportional to the speed of wound healing.